1855
DOI: 10.5962/bhl.title.56616
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of Pliny

Abstract: Gregory's (Dr.) Evidences, Doctrines, and Duties of the Christian Religion. English. In 4 vols. Vol. 1. Thirty Years' War, and Revolt of the Netherlands. Vol. 2. Continwition of the Revolt of the Netherlands; Wallenstcln's Camp ; the Piccolomini ; the Death of Wallensteln; and William Tell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 0 publications
0
49
0
1
Order By: Relevance
“…The clay earth pigments, ochre and sienna for instance, are naturally occurring minerals, principally iron oxides. For what concerns the dispersion of light from prisms, this was a phenomenon described even in the Natural History by Pliny the Elder [5]. Since this book was one of the ancient books that the scholars of the Middle Age used for their treatises on Nature, it is quite probable that Grosseteste experimented with prisms, even if he did not discuss the phenomenon in his treatises.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clay earth pigments, ochre and sienna for instance, are naturally occurring minerals, principally iron oxides. For what concerns the dispersion of light from prisms, this was a phenomenon described even in the Natural History by Pliny the Elder [5]. Since this book was one of the ancient books that the scholars of the Middle Age used for their treatises on Nature, it is quite probable that Grosseteste experimented with prisms, even if he did not discuss the phenomenon in his treatises.…”
Section: Discussionmentioning
confidence: 99%
“…Pliny tells that it was very different from amethysts. The great difference between amethyst and hyacinthos is that "the brilliant violet which is so refulgent in the amethystos, is diluted in the other stone" [5]. John Bostock, who translated the Pliny's History, reports that this could be the name of the oriental amethyst or violet sapphire, not the hyacinthine of the modern English, meaning a stone of a yellowish colour, as in yellow zircon.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, its heyday seems to have lasted only about a century and a half, from the generation of Cicero to the last decades of the 1st century AD. By the early decades of the 2nd century, Corinthian Bronze seems to have been a fashion of the past, for the younger Pliny (the nephew of the encyclopaedist of the same name) describes a newly acquired Corinthian Bronze statuette as an antique (42). By then, the manufacture of Corinthian Bronze had evidently become commercially unattractive, and the Imperial attempts to control its price could only have helped to put a brake on this activity.…”
Section: Corinthian Bronze and Depletion Gildingmentioning
confidence: 99%
“…(2). In another passage, Pliny notes the pleasing appearance that the gold and silver alloying elements lend to Corinthian Bronze (3).…”
Section: Corinthian Bronze and Its Identificationmentioning
confidence: 99%
“…Aristotle claimed that eels emerge spontaneously after the rain, whereas Pliny the Elder suggested that adult eels rub their skin against rocks and the pieces that come off subsequently metamorphose into young eels (Aristotle, 1910;Pliny the Elder, 1855). Furthermore, just over a 100 years ago eel larvae were considered as a separate species, named Leptocephalus brevirostris Kaup, 1856.…”
mentioning
confidence: 99%